Impact of DTG Use During Pregnancy on Birth Outcomes of HIV-Infected Women in the Western Cape, South Africa - Meyer, Jamie (Department of Public Health and Family Medicine, 2026)
Background: The global shift to tenofovir+lamivudine+dolutegravir (TLD) has improved viral suppression in pregnant women living with HIV (WLH) but there are limited data on the combined impact of HIV and maternal body composition on birth outcomes. Methods: We enrolled WLH on TLD and a comparison group of women not living with HIV (WNLH) seeking antenatal care at primary health facilities in Cape Town. Gestational age (GA) was determined via ultrasound by research sonographer; behavioural and demographic data were collected through questionnaires; anthropometry was through clinical examination. Birth outcome data were abstracted from medical records, including pregnancy loss (miscarriage and stillbirth), prematurity (<37weeks GA), low birthweight (LBW) (<2500g), high birthweight (>400g) and size for GA [including small-(SGA) and large-for-GA (LGA) from Intergrowth estimates. Logistic regression models assessed the association between HIV/TLD and birth outcomes adjusting for maternal age, BMI, alcohol use and education; results are reported as adjusted odds ratios (AOR). Results: We followed 1908 women (804 WLH, 1104 HIV-; mean age 28y, median GA at enrolment, 14w; median BMI at enrolment, 31kg/m2 [IQR, 25-35]. Birth outcomes were known for 1869 women (98%) including 65 miscarriages (3.4%), 35 stillbirths (1.9%) and 1769 live births (1735 singletons). Overall rates of prematurity, LBW, HBW, SGA, HBW and LGA were 9.4%, 12%, 13%, 4% and 12%, respectively, and did not differ between WLH and HIV- women. BMI did not affect the association between HIV/TLD and any birth outcome. Independent of HIV/TLD, higher BMI was associated with reductions in prematurity, LBW and SGA. Conclusion: These results suggest few meaningful differences in birth outcomes between WLH on TLD in this setting, where both HIV and obesity are prevalent. Maternal BMI appears to be a more significant driver of birth outcomes than HIV in this cohort.